Menilik Peran Dewan Perwakilan Daerah dalam Pembangunan Daerah Provinsi Jawa Barat dan Daerah Khusus Ibukota Jakarta - Fikri, Muhammad Dzulfikar (UI Scholars Hub, 2022)
The Regional Representative Council (DPD) as a regional representative institution that has a character of representation based on regions is essentially a character of broader representation of the DPR, because the dimension of representation is based on all the people contained in these regions. DPD as a new state institution after the amendment to the 1945 Constitution was initially expected to realize a bicameral system, as a representative body of the people, the DPD has functions as regulated in the 194 5 Constitution. These functions are legislative functions, functions budget, and consideration functions. However, according to the Indonesian constitutional system the authority of the DPD is still very limited. All tasks and authorities of the DPD are limited to aspects that are closely related to the region. In carrying out its role and function as the second chamber in the Indonesian bicameral system, the Regional Representative Council is considered to have some weaknesses. including in terms of accommodating the aspirations of the region and the ineffectiveness of the role of the Regional Representative Council in carrying out all functions that have been given to the DPD by the 1945 Constitution. These constraints have an impact not only at the central level but also at the regional level. The limitations of the DPD also have an impact on regional development and national development.